Radio Navigation Systems for Airports and Airways - Skrypnik, Oleg Nicolaevich; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights the design principles of ground based radio-navigation systems used in solving navigation tasks in the airfield and on air routes. Mathematical correlations are illustrated that describe its operation, peculiarities of disposition, main technical characteristics, generalized structural diagrams as well as the inter-operation with onboard equipment. Examples of building, construction, functional diagrams, and characteristics of Russian made radio-navigation systems are discussed. This book is written for students of electronics and aviation disciplines. It can also be useful for aviation specialists as well as for those interested in air radio-navigation.
Keywords: Aerospace engineering; Astronautics; Wireless communication systems; Mobile communication systems; Microprogramming .; Signal processing; Electronics; Computational intelligence; Aerospace Technology and Astronautics; Wireless and Mobile Communication; Control Structures and Microprogramming; Signal, Speech and Image Processing; Electronics and Microelectronics, Instrumentation; Computational Intelligence